Profil wartości jako miara efektywności działania firmy - Krysiak, Zbigniew (Profile of the Company Value. Efficiency Measure, 2005)
In the presented paper author propose to utilize the profile of the company value to measure the efficiency of the company activity. Profile of the company value can be understood as the probability distribution of the company value. Profile of the company value is an inspirated driver of several risk factors and several value generators. The paper presents relation between risk factors and value of the company. There is proved evidence that the value of the company is influenced by the particular risk factors like credit risk, financial leverage risk and default risk. To support this evidence author presents the empirical research studies based on the equity prices of the companies quoted on the stock exchange in Warsaw. Any correlations between above mentioned variables were performed using the option model based on Merton and KMV assumption points. Conclusions drown from performed studies are that option model is useful tool to quantify the impact of separate particular factors of the value of the company. The complex impact on the company value of the several factors is able to be measured as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 273-285